Capturing snapback in indirect tensile testing using AUSBIT - Adelaide University Snap-Back Indirect Tensile test. (November 2021) - Verma, Rupesh K.; Nguyen, Giang D.; Karakus, Murat; Taheri, Abbas
Abstract: Specimen cracking in a controlled environment is an essential characteristic that is challenging to capture in indirect tensile testing methodologies, including the Brazilian disc test and Ring test. Despite wide popularity, these experiments are incapable of acquiring the actual post-peak behavior and complete load versus displacement response when both load and displacement reversals occur. It is due to the excess strain energy beyond the dissipation capacity of the specimen's center crack, where stress reaches the threshold first, leading to violent dynamic responses that cannot be stabilized using direct displacement control. This study presents the applications of an innovative methodology, named AUSBIT ( Adelaide University Snap-Back Indirect Tensile test ), to stabilize the disc cracking under diametrical compression, using indirect lateral displacement control. The AUSBIT enables us to capture the complete load versus displacement response exhibiting snapback (or class-II), facilitating the analysis of strain energy and dissipation behind the observed snapback behavior. Brazilian disc tests using the AUSBIT were performed successfully on concrete and various rocks, including Hawkesbury sandstone, Iranian Granite, and Bluestone. Acoustic emission (AE) and Digital Image Correlation (DIC) techniques were used to assess the effectiveness of AUSBIT in controlling the localized dynamics. Using this test method, the intrinsic mechanism of strain energy evolution and its influence on the overall snapback behavior, along with the influence of specimen size and material types, can be analyzed with reliable data excluding the dynamic effects.